Critical parameters and mechanism for hydrothermal polyethylene conversion - van de Minkelis, Johan H; de Waart, Anna E; Altink, Rinke M; Vollmer, Ina; Weckhuysen, Bert M (RSC sustainability, 2025)
Hydrothermal conversion can convert plastic materials into smaller hydrocarbons with the use of supercritical water. However, the current knowledge of the process lacks detailed studies on the effects of different reaction parameters, such as temperature and the polymer-to-water ratio. In addition, a detailed analysis of all reaction product fractions is lacking. In this work, a multi-analytical study was performed using polyethylene with different molecular weights. We found that for this polymer, temperatures of 425–450 °C and reaction times of 0.5–2 h are necessary to achieve full conversion with high selectivity towards liquid hydrocarbon species. Apart from acting as a solvent and catalyst, supercritical water also acts as a reactant. The use of D 2 O showed that D-atoms from water molecules were present in the hydrocarbon products formed. This observation shows that hydrothermal conversion proceeds via a radical generation process induced by both the elevated temperature and hydrogen and hydroxyl radicals originating from water. The process with supercritical water lowers the reaction rate compared to pyrolysis at a similar temperature and suppresses the production of coke species. This work investigates the critical parameters for hydrothermal polyethylene conversion via a multi-analytical approach. The mechanism of the process was elucidated with supercritical water acting as a reactant through the formation of radicals.